Associations Between Waiting Times, Service Times, and Patient Satisfaction in an Endocrinology Outpatient Department: A Time Study and Questionnaire Survey. (21st November 2017) - Xie, Zhenzhen; Or, Calvin
The issue of long patient waits has attracted increasing public attention due to the negative effects of waiting on patients' satisfaction with health care. The present study examined the associations between actual waiting time, perceived acceptability of waiting time, actual service time, perceived acceptability of service time, actual visit duration, and the level of patient satisfaction with care. We conducted a cross-sectional time study and questionnaire survey of endocrinology outpatients visiting a major teaching hospital in China. Our results show that actual waiting time was negatively associated with patient satisfaction regarding several aspects of the care they received. Also, patients who were less satisfied with the sociocultural atmosphere and the identity-oriented approach to their care tended to perceive the amounts of time they spent waiting and receiving care as less acceptable. It is not always possible to prevent dissatisfaction with waiting, or to actually reduce waiting times by increasing resources such as increased staffing. However, several improvements in care services can be considered. Our suggestions include providing clearer, more transparent information to keep patients informed about the health care services that they may receive, and the health care professionals who are responsible for those services. We also suggest that care providers are encouraged to continue to show empathy and respect for patients, that patients are provided with private areas where they can talk with health professionals and no one can overhear, and that hospital staff treat the family members or friends who accompany patients in a courteous and friendly way.